Analysis of the Effect of Working Capital Efficiency, Liquidity, and Solvency on Profitability in Manufacturing Companies in the Consumer Goods Industry Sector on the Indonesia Stock Exchange - Fahrul Kahfi (Newinera Publisher, 2022)
In this research, the following objectives are to be achieved: (1) to test and analyze the effect of working capital efficiency on the profitability of manufacturing companies in the consumer goods industry sector that are listed on the IDX; (2) to test and analyze the effect of liquidity on the profitability of manufacturing companies in the consumer goods industry sector that are listed on the IDX. The findings of this research reveal that the variable (1) Net Working Capital Turnover has a very significant influence, which is further supported by the fact that the level of significance attained is lower than the standard employed, namely 1.4 percent as opposed to 5 percent (see Table 1). The level of significance is less than the established standard of significance, which is 0.05 or 5 percent, and the comparison between tcount and ttable, where tcount is 2,283 times greater than ttable, which is 1,990, indicates that the level of significance is less than the established standard of significance.